Multiple timescales of normalized value coding underlie adaptive choice behavior - Jan Zimmermann (Nature Portfolio, 2018)
Previous work has shown that the neural representation of value adapts to the recent history of rewards. Here, the authors report that a computational model based on divisive normalization over multiple timescales can explain changes in value coding driven by changes in the reward statistics.